A fast and accurate technique for determination of moisture content in hevea rubber latex using an insulated monopole sensor - Ansarudin, Farizah; Abbas, Zulkifly; Ismail, Mohammad Aliff (Faculty of Engineering, Universiti Putra Malaysia, 2012)
This paper presents a new insulated monopole sensor technique to determine the amount of moisture content in hevea rubber latex. The conventional oven drying method to determine moisture content in hevea rubber latex is too time consuming and laborious. Using insulated monopole sensor technique, calibration equations have been established relating magnitude and phase of reflection coefficient, conductance and susceptance to moisture content. These equations were in turn used to predict moisture content in rubber latex from microwave measurements. Correlation between the magnitude and phase shift of reflection coefficient, conductance and susceptance with frequency were analyzed for latex moisture content in the range from 36.95% to 82.92%. Comparison results were made between predicted and actual moisture content obtained using conventional oven drying method. Calibration equations based on the magnitude and phase of reflection coefficient, conductance and susceptance were found to be the most accurate within ±5% when compared to conventional oven drying method.